PP-032 Anticipated circuit of anticancer intravenous chemotherapies prescription and preparation in a day hospital: observational study assessing the impact of the new workflow for hospital pharmacy. (25th February 2017) - Langhendries, C; Spinewine, A; Soumoy, L; Hecq, JD; Andre, M; D'Hondt, L; Duplaquet, F; Jamart, J; Gillet, P
Abstract : Background: As anticancer intravenous chemotherapies (AIVC) are high risk medications, there are different ways of securing the preparation circuit. In this context, an anticipated circuit of prescription and preparation (ACPP) for AIVC was developed. Purpose: To evaluate the impact of the ACPP protocol on the quality and timing of medication preparations with the primary objective of 40% decrease in mean daily variances. Material and methods: 210 patients were included in the before group and 207 patients in the after group (19% of them were included in the ACPP protocol). A 21% decrease in mean daily variances was observed with the ACPP (p=0.11, SD ranging from 1.27 to 0.83 (p=0.025)). The patient's mean waiting time decreased from 128 to 114 min (p=0.005) between the before/after groups and to 60 min for the ACPP (p < 0.001). 1 of the 174 bags was lost in the ACPP. Results: The mean daily variance enabled us to observe an improvement in the timing of production without reaching our 40% decrease objective. The mean waiting time significantly decreased but remained above 30 min. The losing rate in the ACPP protocol was <2%, as desired. Failure to reach our preset objectives can be explained by the fact that the ACPP is a new concept in the clinic. Conclusion: The ACPP helped to improve pharmacy activities and to decrease patient waiting times but also helped maintain similar safety and avoided losses. However, the study should be conducted on a larger cohort and over a longer period to confirm the impact of the project. References and/or acknowledgements: Scotte F, Oudard S, Aboudagga H, et al. A practical approach to improve safety and management in chemotherapy units based on the PROCHE–programme for optimisation of the chemotherapy network monitoring programme. Eur J Cancer2013;49:541–4. No conflict of interest